2021
DOI: 10.1108/gkmc-03-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

The essential skills and competencies of LIS professionals in the digital age: alumni perspectives survey

Abstract: Purpose The librarianship profession has gone through many changes over time, more so with the emergence of digital technologies. To thrive in the library and information science (LIS) profession, professionals must have knowledge, skills, competencies and abilities to perform their job duties. The purpose of this paper was to identify essential knowledge, skills and abilities (KSAs) for the LIS professionals. Design/methodology/approach The targeted survey group for the study were alumni of ten LIS schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Sewant and Yadav (2020) assessed knowledge, proficiency and expertise of smart librarians found that library professionals rated personal skills and generic skills as good and excellent and they were competent with few technical skills such as advance database management, advance web technology, content management system, educational copyright knowledge, and e-books acquisition and maintenance. Yadav (2022) observed that digital tools and technologies have brought sea change in the library profession and identified core competencies required for the library profession after consulting large number of research papers published in international journals. They were: traditional library skills, research skills, computing skills, data management skills, and soft skills.…”
Section: Professional Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sewant and Yadav (2020) assessed knowledge, proficiency and expertise of smart librarians found that library professionals rated personal skills and generic skills as good and excellent and they were competent with few technical skills such as advance database management, advance web technology, content management system, educational copyright knowledge, and e-books acquisition and maintenance. Yadav (2022) observed that digital tools and technologies have brought sea change in the library profession and identified core competencies required for the library profession after consulting large number of research papers published in international journals. They were: traditional library skills, research skills, computing skills, data management skills, and soft skills.…”
Section: Professional Competenciesmentioning
confidence: 99%
“…Chawner and Oliver (2013) stress that apart from enhancing digital literacy, other skills such as managerial, communication, interpersonal and research are also equally important for librarians to manage and provide specialized information services. Yadav (2022) depicts that the most important task of the library professionals is to apply their specialized skills to identify the right source and share among the users. Apart from possessing technological expertise, the author suggested the librarians to posses other skills such as critical judgment skills, managerial skills, research skills.…”
mentioning
confidence: 99%
“…To understand exactly what soft skills are, [61] describes these as communicative qualities that improve interaction efficiency or a person's ''Emotional Intelligence Quotient". [59] outlined some important soft skills including effective communication and interpersonal skills, empathy and emotional intelligence, analytical thinking and innovation, conflict management, and problem-solving skills. teamwork and collaboration.…”
Section: Implication Of Industry 50 For Competenciesmentioning
confidence: 99%
“…Much of this work examines competencies in relation to specific contexts. On a national level, studies of librarian professional competencies have been done in Pakistan (Khan & Mahmood, 2013;Ismail & Khan, 2021), India and South Asia (Kaur, 2015;Yadav, 2022), the United States (Goodsett & Koziura, 2016;Saunders, 2019;Hu et al, 2022;Saunders, 2015); Japan (Toshimori, Mizoue, & Matsumoto 2011), and South Africa (Bothma & Britz, 2000). There has also been a focus on competencies related to specific information work including competencies for data professionals (Kim, 2016;Harris-Pierce & Quan Lui, 2012), health information professionals (Pandolfelli, et al;, and knowledge management (Husain & Nazim, 2015) workers.…”
Section: Literature Reviewmentioning
confidence: 99%